The potential of Nephrolepis biserrata fern as ground cover vegetation in oil palm plantation - Halus Satriawan; ZAHRUL FUADY; ERNAWITA ERNAWITA (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Satriawan H, Fuady Z, Ernawita. 2021. The potential of Nephrolepis biserrata fern as ground cover vegetation in oil palm plantation. Biodiversitas 22: 4808-4817. Nuisance plants or weeds are commonly found in agricultural landscapes including in oil palm plantations. Despite being considered as weeds, several of them have the potential to be used as ground cover vegetation including Nephrolepis biserrata (Sw). Schott. This fern species exhibits beneficial characteristic as ground cover plant especially in terms of the contribution of organic matter and soil moisture through the prevention of evapotranspiration. The objective of this research is to explore the potential of N.biserrata as ground cover vegetation in oil palm plantations based on the assessment of its ecological characteristics regarding the growth and decomposition rate, tolerance to shade, organic contents and carbon accumulation. The split plot experimental design was used with the age of oil palm plants was used as main plot while in the sub-plots the spacing of N. biserrata was used at three varying distances 10x10cm, 20x20 cm, and 30x30 cm, each treatment had three replicates. Nine parameters observed were the percentage of growth, the percentage of ground cover, plant height, fronds number per plant, leaves number per plant, Leaf Area Index, dry weight (g), nutrient content in plant tissue, and potential carbon stock. Results showed that N. biserrata showed rapid growth in covering the ground surface (8-12 weeks after planting), had rapid decomposition rate (30-60 days), tolerant to shading which was characterized by the highest percentage of growth up to 81.16% and covering area up to 95.9%, accumulated organic contents of N (1.23-1.53%), P (0.18-0.22%), and K (1.4-1.67%), respectively. In addition, total dry weight biomass obtained was 27.1 ton/ha, accumulated carbon in plant of 0.9 tons C/ha/year, and amount of soil carbon stock 76.4-97.4 tonnes/ha/year. The results of this study suggest that Nephrolepis biserrata is a potential plant to be utilized as a ground cover plant in oil palm plantations.